Modern approaches to the genetic identification of farm animal breeds (review) - A. Y. Krivoruchko; A. V. Skokova; O. A. Yatsyk; A. A. Kanibolotskaya (Аграрная наука Евро-Северо-Востока)
To improve the breed characters of farm animals, there is the need for breeding based on reliable information about the particular breed of animals, which is the key to high-quality breeding work. In this regard, there is a need to search for new methods of reliable identification of the breed of animals. The article presents an analysis of methods based on the achievements of modern genetics, which are used to obtain more accurate information when determining the breed of ani-mals. A brief description of methods for determining the species and breed identification of animals based on molecular DNA markers is given. Methods based on the study of polymorphism of mitochondrial DNA and microsatellites are analyzed. Spe-cial attention in this review is paid to the latest and most promising achievements in the field of high-performance genotyping technologies based on single nucleotide polymorphism (SNP). The analysis of the literature sources has shown that each breed of farm animals is characterized by its unique genetic structure, which should provide an objective result when deter-mining the breed of the animal.